Formation of AraC-DNA sandwiches. - Carra, J H (1993)
With the use of special DNA binding sites, but not the natural aral binding site, the dimeric AraC protein can be forced to make sandwich structures in which two DNA molecules are joined by two AraC protein dimers. Apparently one subunit from each dimer contacts each DNA molecule in an extended structure. These sandwich structures form only in the absence of arabinose. This behavior is consistent with the protein's ability to form DNA loops by binding to separated half sites in the absence of arabinose and its preference for binding to adjacent half-sites in the presence of arabinose.